USE OF TEXT READING TO DEVELOP SPEAKING SKILLS (Konferensiyalar | Conferences, 2024)
This article focuses on how vocabulary wealth relate to spoken words and finally how reading contributes to speech. The importance of vocabulary, which facilitates speaking skills, has been a major resource in the development of reading skills. Therefore, providing improvement in word knowledge through wide reading has the potential for providing improvement in speaking skills.